2006
DOI: 10.1002/ajmg.b.30371
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of alpha‐2A adrenergic receptors in attention deficit hyperactivity disorder: Radioligand binding and polymorphism studies

Abstract: Neuropharmacological and genetic association studies have implicated norepinephrine and adrenergic receptors in the pathogenesis of ADHD. The purpose of this study was to compare genetic association studies of three polymorphisms of the alpha-2A adrenergic receptor gene (ADRA2A) with radioligand binding studies of the alpha-2A adrenergic receptor protein in platelets from a sample of children without or with ADHD. The pediatric subjects ranged from 6 to 18 years of age. A thorough clinical assessment of each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 57 publications
1
25
0
1
Order By: Relevance
“…In fact, clonidine, which decreases NE activity, has been reported to be of benefit in ADHD and is now in a Phase III clinical trial for treatment of ADHD (http://clinicaltrials.gov/show/NCT00031395). Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…In fact, clonidine, which decreases NE activity, has been reported to be of benefit in ADHD and is now in a Phase III clinical trial for treatment of ADHD (http://clinicaltrials.gov/show/NCT00031395). Our evidence suggests that a decrease in α2-adrenergic autoreceptor control of NE activity underlies noradrenergic hyperfunction in our rat model of prenatal cocaine, so it is interesting that a similar deficit appears to occur in the spontaneously hypertensive rat model of ADHD (Russell, 2002) and that a decreased density and decreased affinity of binding to α2-adrenergic sites have been reported in ADHD (Shekim et al, 1994;Deupree et al, 2006). Moreover, there is evidence supporting association and linkage of α2A-adrenergic receptor gene polymorphisms with ADHD (Park et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…Since this initial study, nine independent studies have been published examining the association of ADHD with this SNP and additional polymorphisms within ADRA2A (Bobb et al 2005;Brookes et al 2006a;Cho et al 2008b;Deupree et al 2006;Guan et al 2008;Park et al 2005;Roman et al 2003;Schmitz et al 2006;Stevenson et al 2005). In the present review, we conducted a meta-analysis of studies testing for association between ADHD and 3 ADRA2A polymorphisms (rs1800544, rs1800545, and rs553668).…”
Section: Alpha 2a Adrenergic Receptor (Adra2a)mentioning
confidence: 99%
“…For the meta-analysis of association between childhood ADHD and the ADRA2A MspI restriction polymorphism (rs1800544), data from Wve TDT (Brookes et al 2006a;Deupree et al 2006;Park et al 2005;Wang et al 2006;Xu et al 2001) and six Case-Control/HHRR (Bobb et al 2005;Cho et al 2008b;Guan et al 2008;Roman et al 2003;Schmitz et al 2006;Stevenson et al 2005) studies were included, with the G allele considered the "high-risk" allele based on previous research (Park et al 2005). Results of this meta-analysis, shown in Fig.…”
Section: Alpha 2a Adrenergic Receptor (Adra2a)mentioning
confidence: 99%
“…According to a recent study by Schmitz et al [2006], those subjects who were homozygous for the G allele had significantly higher odds ratios for the inattentive subtype of ADHD than did those with other genotypes (C/C þ C/G genotypes). With respect to the DraI polymorphism, Park et al [2005] reported the preferential transmission of the T allele of this polymorphism in children with ADHD combined subtype, and Deupree et al [2006] observed significant linkage disequilibrium with this polymorphism and the inattentive or hyperactive phenotypes of ADHD.…”
Section: Introductionmentioning
confidence: 99%